Mindfulness meditation and bimanual coordination control: study of acute effects and the mediating role of cognition - Devillers-Réolon, Louise; Temprado, Jean-Jacques; Sleimen-Malkoun, Rita (Frontiers in Psychology, 2023)
Introduction Mindfulness meditation (MM) involves and benefits cognitive functioning, especially attention and inhibition processes, which are also implicated in the control of complex motor skills, such as bimanual coordination. Thus, MM practice could potentially enhance bimanual coordination control through its cognitive benefits. Accordingly, in this study, we investigated the acute effects of a brief MM session on bimanual coordination dynamics, attention, and inhibition abilities, as well as the mediation link between MM’s cognitive and motor improvements. Methods Healthy meditation-naïve (novices, n = 29) and meditation-experienced participants (meditators, n = 26) were randomly assigned to either an active control intervention (attentive listening to a documentary podcast) or a MM intervention (breathing and open monitoring exercise), both lasting 15 min. In the motor domain, pre- and post-tests assessed participants’ ability to intentionally maintain the anti-phase coordination pattern at maximal movement frequency and resist the spontaneous transition to the in-phase pattern. In the cognitive domain, the participants’ attentional, perceptual inhibition and motor inhibition abilities were assessed. Results Following both interventions, meditators and novices improved the stability of their anti-phase coordination pattern (p = 0.034, ηp2 = 0.10) and their attentional performance (p’s < 0.001, ηp2 > 0.40). Only following the MM intervention, meditators and novices improved their ability to intentionally maintain the anti-phase pattern by delaying or even suppressing the spontaneous transition to in-phase (p’s < 0.05, ηp2 ≥ 0.11), and improved concomitantly their motor inhibition scores (p = 0.011, ηp2 = 0.13). No effects were found on perceptual inhibition. The increase in motor inhibition capacities did not however statistically mediate the observed acute effects of MM on bimanual coordination control. Conclusion We showed that a single MM session may have acute benefits in the motor domain regardless of the familiarity with MM practice. Although these benefits were concomitant to enhanced attentional and motor inhibition abilities, no formal mediation link could be established between the observed motor and cognitive benefits. This study paves the way for the investigation of the mechanisms underlying MM effects on motor control, as well as longer-term benefits.